NILAI FINANSIAL DAN POTENSI KONFLIK PERIKANAN UDANG MANTIS DI KUALA TUNGKAL, JAMBI - Nofrizal; Ramdhani, Farhan; Jhonnerie, Romie (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
Mantis shrimp is an export commodity that caught by fishermen in Kuala Tungkal. Mostly, the fishermen use gillnet as their main fishing gear. However, this fishing effort shares open access and common property to be its aquatic resources with other fishing businesses that may bring potential conflicts related to fishing areas, utilization of aquatic resources, fishing gear, etc. Thus, this current study aims to analyze economic value and potential conflicts in mantis shrimp catch in Kuala Tungkal. A survey method was applied as the research method. From 2015 to 2017, the export volume and value of shrimp commodities continued to increase. The results show that profit value (π) possessed by catching mantis shrimp is Rp637.500,00 per trip, R/C 5.6 and PP 39 trips showing a good financial value and potential to be developed. Meanwhile, potential conflicts in catching mantis shrimp tend to be low since there is no overlapping fishing area for each fishing gear operated by different aquatic resource users. It means that the operation of fishing gear has been set well by the community of fishing businesses in that area so that the potential for social conflicts between aquatic resources users is also low.